Nannophlebia leoboppi sp nov., a new dragonfly species from New Guinea (Odonata: Anisoptera: Libellulidae) - Orr, Albert G.; Kalkman, Vincent J. (Zootaxa, 2015)
Nannophlebia leoboppi sp. nov. is described and figured based on a male specimen collected in the Star Mountains of Central New Guinea. This relatively large representative of its genus is compared with its probable nearest relative, N. antiacantha Lieftinck, 1963, which is also partially figured. The new species brings the total number of Nannophlebia species to 25.